Patched 1 and Patched 2 redundancy has a key Role in regulating epidermal differentiation - Adolphe, C.; Nieuwenhuis, E.; Villani, R.; Li, Z.; Kaur, Pritinder; Hui, C.; Wainwright, B. (Nature Publishing Group, 2014)
The Patched 1 (Ptch1) receptor has a pivotal role in inhibiting the activity of the Hedgehog (Hh) pathway and is therefore critical in preventing the onset of many human developmental disorders and tumor formation. However, the functional role of the mammalian Ptch2 paralogue remains elusive, particularly the extent to which it contributes to regulating the spatial and temporal activity of Hh signaling. Here we demonstrate in three independent mouse models of epidermal development that in vivo ablation of both Ptch receptors results in a more severe phenotype than loss of Ptch1 alone. Our studies indicate that concomitant loss of Ptch1 and Ptch2 activity inhibits epidermal lineage specification and differentiation. These results reveal that repression of Hh signaling through a dynamic Ptch regulatory network is a crucial event in lineage fate determination in the skin. In general, our findings implicate Ptch receptor redundancy as a key issue in elucidating the cellular origin of Hh-induced tumors.